The Hydrographical Characteristics And The Economical Potential Of Anamur (Dragon) Creek (Mersin) - Sunkar, Murat; Uysal, Ahmet (Istanbul Univ, Fac Letters, Dept Geography, 2014)
In this study, the hydrographical characteristics and the economical potential of Anamur Stream have been investigated. Anamur Stream which takes its source from Taseli Plateau is located on the southernmost corner of Taseli Peninsula. Anamur Sream which is one of the most important streams of Taseli Plateau facing to Mediterranean Sea discharges from the east of Anamur into the sea. The monthly average flow rate of Anamur Creek, which has a non -uniform flow pattern, is 24.43 m3 / sec. The precipitation is important for Anamur Creek which is fed with karstic sources. The flow rate which increases with the rainfalls in winter reaches to the maximum level with the snow melt in winter. It decreases to the minimum level in summer depending on the drought. The fact that the flow is low during summer and high during winter and spring directly relates with the climatic characteristics. Local climate characteristics observed around Anamur enabled the production of agricultural products with high-profit like banana and strawberry. There has been an increase in the production and income with the opening of other agricultural areas in the basin to irrigation apart from Anamur Plain. A large number of ponds and dams have been constructed on the stream in order to meet water requirements during the dry period. A major part of these ponds and dams are used in order to meet the water requirement of Anamur locality. In recent years, projects for meeting water requirements of the Turkish Republic of Northern Cyprus (TRNC) have been put into practice. For this purpose, Anamur Creek has been chosen due to its high potential and its closeness to the TRNC.
Keywords: Anamur Stream; Anamur Plain; Mediterranean Sea; Hydrographical Characteristics; Taseli Plateau